2008
DOI: 10.1093/ndt/gfn466
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcifications, vertebral fractures and mortality in haemodialysis patients

Abstract: Background. Vascular calcifications and the bone fractures caused by abnormal bone fragility, also called osteoporotic fractures, are frequent complications associated with chronic kidney diseases (CKD). The aim of this study was to investigate the association between vascular calcifications, osteoporotic bone fractures and survival in haemodialysis (HD) patients.Methods. A total of 193 HD patients were followed up to 2 years. Vascular calcifications and osteoporotic vertebral fractures (quoted just as vertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
95
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 63 publications
12
95
1
3
Order By: Relevance
“…In an interesting clinical study, Park et al (83) found that age and hypertension were independent risk factors for the classification of CAC scores that represented the degree of AC (83). In CKD patients followed up to 2 years, it was shown that age, diabetes and smoking were significantly associated with a higher prevalence of AC (86). However, in recent years, the nontraditional risk factors, e.g., oxidative stress, inflammation, malnutrition, fibroblast growth factor 23 (FGF-23), and Klotho, are gradually arousing interest (16) because the traditional risk factors linked to AC are often correlated with these deregulated nontraditional risk factors in CKD.…”
Section: Risk Factors Of Ac In Ckdmentioning
confidence: 99%
“…In an interesting clinical study, Park et al (83) found that age and hypertension were independent risk factors for the classification of CAC scores that represented the degree of AC (83). In CKD patients followed up to 2 years, it was shown that age, diabetes and smoking were significantly associated with a higher prevalence of AC (86). However, in recent years, the nontraditional risk factors, e.g., oxidative stress, inflammation, malnutrition, fibroblast growth factor 23 (FGF-23), and Klotho, are gradually arousing interest (16) because the traditional risk factors linked to AC are often correlated with these deregulated nontraditional risk factors in CKD.…”
Section: Risk Factors Of Ac In Ckdmentioning
confidence: 99%
“…Moreover, vascular calcification is frequently associated to bone mass disorders, which suggests that factors involved in the regulation of both entities could be linked. 1,2 Vascular smooth muscle cells (VSMCs) have the same mesenchymal origin as osteoblasts, and they are able, in the presence of several stimuli, including uremia, to transdifferentiate into osteoblastic cells in response to signals coming from the internal milieu, extracellular matrix components, and biochemical and physical factors. 3,4 This phenotypic modulation is tightly regulated and involves the loss of expression of several muscle-related proteins of the VSMCs and the gain of expression of bone-related proteins accompanied by macroscopic structural changes, such as calcifications.…”
mentioning
confidence: 99%
“…These changes in normal phosphate homeostasis lead in part to the manifestations of the entity known as CKD-mineral bone disorder (CKD-MBD) (1). Epidemiologic data have identified an association between the hyperphosphatemia of CKD-MBD and patient-based outcomes of vascular calcification, myocardial dysfunction, and mortality (2)(3)(4)(5).…”
mentioning
confidence: 99%